2019
DOI: 10.1071/hc18105
|View full text |Cite
|
Sign up to set email alerts
|

‘We're kidding ourselves if we say that contraception is accessible’: a qualitative study of general practitioners’ attitudes towards adolescents’ use of long-acting reversible contraceptives (LARC)

Abstract: INTRODUCTIONAdolescents’ uptake of long-acting reversible contraceptives (LARCs) in New Zealand is low. We created the concept of a proactive LARC provision programme to overcome barriers to LARC uptake. Previously, this concept was discussed with adolescents and positively received. Lack of provider awareness is a barrier to LARC use identified in previous research and by adolescents. AIMWe sought the views of general practitioners (GPs) to gauge whether LARCs and their proactive promotion for use in adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Barriers remain to effective access to contraceptives for adolescents. 1,2 Current provision of contraception to NZ adolescents is reactive (rather than proactive) and not focused on long-acting reversible contraceptives (LARCs), and therefore may not be as effective as it could be. 1,2,5 Of NZ adolescents aged 17 and over, 40.5% have ever had sex, 6 but only 52% of sexually active adolescents in NZ use contraception consistently -consistent adolescent contraception use is actually decreasing.…”
Section: Adolescent Contraceptive Access In Nzmentioning
confidence: 99%
See 3 more Smart Citations
“…Barriers remain to effective access to contraceptives for adolescents. 1,2 Current provision of contraception to NZ adolescents is reactive (rather than proactive) and not focused on long-acting reversible contraceptives (LARCs), and therefore may not be as effective as it could be. 1,2,5 Of NZ adolescents aged 17 and over, 40.5% have ever had sex, 6 but only 52% of sexually active adolescents in NZ use contraception consistently -consistent adolescent contraception use is actually decreasing.…”
Section: Adolescent Contraceptive Access In Nzmentioning
confidence: 99%
“…17 In qualitative research, PCP for LARCs rather than for all methods was discussed. 1,2 The question of which contraceptives to offer remains unanswered.…”
Section: Which Contraceptives?mentioning
confidence: 99%
See 2 more Smart Citations
“…We also have an article about long-acting reversible contraception (LARC) for adolescents. 10 Duncan et al explore the potential acceptability to GPs of a proactive approach, where they would routinely offer LARCs to adolescents requesting contraception. Along the way, the researchers found that their participating GPs were often unaware that LARCs are suitable for adolescents and consequently do not routinely offer this form of contraception.…”
mentioning
confidence: 99%